Effect of service quality and online servicescape toward customer satisfaction and loyalty mediated by perceived value. Issue 1 (March 2021) - Hanafi,; Widyawati, R; Widowati, A S
Abstract: Application-based transport or online ojek has been main trends in Indonesia. It gives solution to public in rush hours especially in urban area. Even though they are needed but many customers have complaint about their services. The purposes of this study are observing the operator effort to maintain customer satisfaction and loyalty. It evaluated customer response to determine the cause of the satisfaction and loyalty especially for the construct of service quality and online servicescape. In addition, it brings new construct as mediation variable of perceived value to strengthen the relationship among the variables. This study found the new relationship among service quality and online servicescape to strengthen customer satisfaction and loyalty. By collecting the customers from Jakarta region as respondent's, this study tested their perception about the online service delivery and their effect to the loyalty. Some suggestion and direction also given to expand the research as discussion topic.